Public drinking, social connection and social capital: A qualitative study. (17th July 2013) - Manton, Elizabeth; Pennay, Amy; Savic, Michael
Abstract : Social isolation is a risk factor for morbidity and mortality which has resulted in calls for facilitating social connection to be a public health priority, especially in socioeconomically disadvantaged population groups. While previous research has explored the role that social connection played in diverse domains, including Skid Row drinkers from the 1950s to the 1970s, its role in the lives of public drinkers has been otherwise neglected. Laws prohibiting the public drinking of alcohol are widely implemented around the world but have been the subject of very little social analysis. A recent evaluation of public drinking laws in three urban districts of Melbourne, Australia, sought the perspectives of police, council officers, outreach workers, traders, community members and public drinkers in evaluating the impact and effectiveness of the laws; this article seeks to foreground the public drinkers' voice. Qualitative interviews with public drinkers were analysed for relevance to the theme of "social connection". Themes arising from the analysis indicated a strong sense of family or community amongst drinkers and frequent organisation of drinking groups along ethnic lines, as well as the provision of bonding social capital. The benefits of providing public drinkers with a legitimate and appropriate public space to promote existing social connections while undertaking a favoured activity, drinking alcohol, are discussed. At a time when fostering social connection is identified as a key public health strategic direction, the needs of public drinkers in this respect should be considered.